Biodiesel Production from Sudanese Jatropha curcas Seed by The Alkali-Catalyzed Transesterification Process and Its Analysis by Gas Chromatography - Arij Mahmoud Ahmed Abdalla; Handajaya Rusli; Muhammad Bachri Amran (Universitas Pakuan, 2022)
Sudan is highly dependent on diesel. Diesel is used in agriculture machines, transportation, and other applications. This study has been carried out to produced biodiesel from Jatropha curcas seed oil. Jatropha was chosen because it is not edible, therefore it will not pose a new problem to humans regarding food competition. This research successfully extracted oil from Jatropha curcas seed using n-hexane solvent with yield 39%. The oil than converted to biodiesel by alkaline transesterification process with a conversion yield 92 %. The properties such as flash point, acid value, viscosity, iodine value, density, copper corrosion, cetane number, sulphated ash, pour point, free glycerol, and total glycerol contents were 174 oC, 0.17 mg KOH/g, 8.912 mm2/s, 102 g I2/100 g, 895.8 kg/m3, class1, 51, 0.0047 %, -3 oC, 0.01 %,0.03 %, respectively. These quantities obtained were met most of the biodiesel standards that are ASTM D6751, EN14214, and ASTM D975. The GC data showed the fatty acid methyl ester (FAME) has a 12-20 carbon chain and still has monoglycerides, diglycerides, and triglycerides.